2007
DOI: 10.1002/app.27117
|View full text |Cite
|
Sign up to set email alerts
|

Rapid replication of nanostructures made with a polymer using simple injection molding

Abstract: It is possible to fabricate nanostructures of 25.5 nm by replication using injection molding. In this study, a silicon calibration grating was used as a mold insert to replicate high-quality nanostructures with a simple custom-made injection machine. The replicated grating with 25.5-nm nanofeatures made with a polymer was of high quality when a high mold temperature was employed and the mold was evacuated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Mold temperature is one of the most import parameters for injection molding because it has a direct influence on the part quality and molding cycle time. Theoretical and experimental studies in literatures1–8 have shown that a high mold temperature not only has a great positive effect on the surface appearance, strength, size, and shape accuracy of the molded part, but also decreases the required injection pressure and clamping force of the molding machine. But the corresponding long cooling time resulting from the high mold temperature decreases the productivity and hence increases the costs.…”
Section: Introductionmentioning
confidence: 99%
“…Mold temperature is one of the most import parameters for injection molding because it has a direct influence on the part quality and molding cycle time. Theoretical and experimental studies in literatures1–8 have shown that a high mold temperature not only has a great positive effect on the surface appearance, strength, size, and shape accuracy of the molded part, but also decreases the required injection pressure and clamping force of the molding machine. But the corresponding long cooling time resulting from the high mold temperature decreases the productivity and hence increases the costs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lin et al1 reported that the luminance of LGPs showed a strong correlation with the depth of the melt filling of the v‐grooves. Injection molding (IM) is one of the most common processes for manufacturing microfeatured parts 2–7. A significant advantage of IM is that it can produce complex geometries during one automated process.…”
Section: Introductionmentioning
confidence: 99%